BRINE SHRIMP LETHALITY ASSAY AND LARVICIDAL ACTIVITY OF N-HEPTADECYL-N-(8-OCTA-1, 3-DIENE-6-YNYL)AMINE (C25H44N) ISOLATED FROM COMBRETUM MOLLE R. (FUDMA JOURNAL OF SCIENCES, 2021)
The extracts of leaves of Combretum molle were tested against the larvae of Artemia salina, i.e. Brine Shrimp Lethality Test (BST) and Culexquinquefasciatus Say (filaria disease vector) i.e. Larvicidal Test, using crude ethanol, n-hexane, chloroform, ethyl acetate, and methanol extracts. The methanolic extract proved to be the most effective in inducing complete lethality at minimum doses both in the BST and the Larvicidal activity test. The LC50Â values obtained are 24.85 Âµg/ml and 0.4Âµg/ml respectively. The Bioactivity result was used to guide the column chromatography which afforded the pure compound ACM 2 which was not active in the BST with LC50 value of 1259 Âµg/ml but was active in the Larvicidal activity test with LC50 value 15.14 Âµg/ml.  ACM 2 was proposed to be N-heptadecyl-N-(8-octa-1, 3-diene-6-ynyl)amine (C25H44N).
Keywords: Brine Shrimp, Larvicidal, Combretum molle, Artemia salina, Culexquinquefasciatus Say